2018
DOI: 10.3390/app8122615
|View full text |Cite
|
Sign up to set email alerts
|

Considering the Life-Cycle Cost of Distributed Energy-Storage Planning in Distribution Grids

Abstract: In the face of the radical revolution of energy systems, there is a gradually held consensus regarding the adoption of distributed renewable energy resources, represented by Photovoltaic (PV) and wind generation. Consequently, the distributed Energy Storage Systems (ESSs) have become increasingly important in the distribution networks, as they provide the arbitrage and ancillary services. Determining the optimal installation site and the capacity of the distributed ESSs will defer the network reinforcements, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In other words, the allocation scheme of ESS with reactive power compensation saved 41% of the average annual cost compared with the scheme without considering reactive power contribution. Comparing the optimization method with the authors' previous research proposed in [60], results are shown in Table 5. The two models were designed to solve the problem of DNs voltage fluctuations caused by the increase of DG penetration, but ESS arbitrage operation and the reactive power of PCS are not considered in [60].…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…In other words, the allocation scheme of ESS with reactive power compensation saved 41% of the average annual cost compared with the scheme without considering reactive power contribution. Comparing the optimization method with the authors' previous research proposed in [60], results are shown in Table 5. The two models were designed to solve the problem of DNs voltage fluctuations caused by the increase of DG penetration, but ESS arbitrage operation and the reactive power of PCS are not considered in [60].…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…Therefore, when DCM is used for UUT construction cost allocation, the direct-laying cost of pipeline should be calculated in a specific time period. In this paper, the time period is set to the life cycle of UUT for the reason that life cycle cost theory considers all stages of UUT from planning, construction, operation to retirement, avoiding decision-making being limited to a certain period of time [18]. After discounting the direct-laying cost of pipelines in the life cycle to the present value, the DCM based cost allocation index of pipeline i can be expressed as:…”
Section: The Life Cycle Direct-laying Cost Methodsmentioning
confidence: 99%
“…It can be seen from Equation 17that α i is proportional to the payback period P i , and inversely proportional to the net investment income and the cost-benefit ratio (i.e., the ratio of the investment income to the allocated UUT construction cost). Equation (18) denotes that the payback period P i is the maximum value of time t that the net investment income within t is equal to the allocated cost of pipeline company i.…”
Section: Comprehensive Decision-making Mechanism Of Uut Cost Allocatimentioning
confidence: 99%
“…The life cycle cost of a distribution network infrastructure project is composed of initial investment costs, operation and maintenance costs, waste and environmental cost, and failure costs [18]:…”
Section: ) Life Cycle Costmentioning
confidence: 99%